A Review on Agronomic, Phytochemical and Pharmacological Aspects of Cannabis (Cannabis sativa L.) - S Asadi; H Moghadam; H Naghdi Badi; MR Naghavi; SAR Salami (Institue of Medicinal Plants, ACECR, 2019)
Cannabis (Cannabis sativa L.), commonly known as hemp, is an annual herb belongs to the family Cannabacea. The seeds of this plant have considerable content of oil and unsaturated fatty acids, and its fiber is used in the paper and textile industries. Tetrahydrocannabinol and cannabidiol are main cannabinoid compounds of this plant, which have high importance for their well-known pharmaceutical properties. Therapeutic effects of secondary metabolites of hemp on different diseases, such as cancer, Multiple Sclerosis (M.S.), and AIDS and their anxiety and palliative characteristics have been reported in several studies. Considering oil content, and therapeutic and industrial properties of the hemp as well as, its high diversity in Iran, more studies are needed to better recognize this plant and the economic production of its therapeutic compounds. In the present paper, a comprehensive review of agronomic, therapeutic and phytochemical characteristics of hemp is presented.